The nitrite reductase encoded by nirBDs in Pseudomonas putida Y-9 influences ammonium transformation - Huang, Xuejiao; Luo, Yuwen; Luo, Luo; Xie, Deti; Li, Zhenlun (Frontiers in Microbiology, 2022)
It is unknown whether nirBDs, which conventionally encode an NADH nitrite reductase, play other novel roles in nitrogen cycling. In this study, we explored the role of nirBDs in the nitrogen cycling of Pseudomonas putida Y-9. nirBDs had no effect on organic nitrogen transformation by strain Y-9. The △nirBD strain exhibited higher ammonium removal efficiency (90.7%) than the wild-type strain (76.1%; P < 0.05) and lower end gaseous nitrogen (N2O) production. Moreover, expression of glnA (control of the ammonium assimilation) in the △nirBD strain was higher than that in the wild-type strain (P < 0.05) after being cultured in ammonium-containing medium. Furthermore, nitrite noticeably inhibited the ammonium elimination of the wild-type strain, with a corresponding removal rate decreasing to 44.8 %. However, no similar impact on ammonium transformation was observed for the △nirBD strain, with removal efficiency reaching 97.5 %. In conclusion, nirBDs in strain Y-9 decreased the ammonium assimilation and increased the ammonium oxidation to nitrous oxide.